A case study of music instruction according to E. Willems' pedagogy in children with intellectual disabilities: Its impacts on music abilities and language skills. (May 2019) - Smolej Fritz, Barbara; Peklaj, Cirila
The aim of this case study was to explore the effects of music instruction according to the E. Willems teaching method on the music abilities and language skills in students with intellectual disabilities (ID). Eight students with ID (average age 9.64 years) participated in the study. They attended 35 music lessons during the school year. Each lesson included tasks for developing four domains: auditory perception, rhythm, singing songs and natural body movement. We developed the tasks for measuring music abilities and language skills and applied them three times: before the music training, immediately after the training and in delayed measurement 10 months after the training. Results showed a significant improvement in the music abilities in rhythm between the first and the second measurements. The improvements between the first two measurements were also found in language skills, in following instructions and in discrimination and repetition of phonemes in pairs. The research method used does not allow for the generalization of results, but it is the first step in empirical research into the effects of music instruction according to the principles of E. Willems' pedagogy in children with ID.